Pengaruh Profitabilitas dan Komite Audit terhadap Audit Report Lag pada Perusahaan Sub Sektor Property dan Real Estate (2017-2018) - Samuel Parlindungan Silalahi; Harman Malau (Universitas Batanghari Jambi, 2020)
This study aims to determine the effect of profitability and audit committee on audit report lag of companies listed on the Indonesia Stock Exchange in the property and real estate sub sector in 2017-2018. This study uses descriptive methods in finding relationships between variables that provide a detailed description of a phenomenon by conducting linear regression analysis. The method of collecting data uses a passive participatory observation method where the researcher observes but is not directly involved in the activity. Through this method has been carried out by studying, classifying, and analyzing secondary data in the form of independent auditor's reports, financial reports and other information related to the scope of this research. Audit report lag, which is the time difference that occurs when the end of the fiscal year with the date of issue in the audit report. This variable is the dependent variable that is measured by the interval of the number of days between the date of the financial statements until the date the auditor's report is signed. The variables that affect are profitability and the audit committee. Profitability will be measured using the ratio of Return on Assets (ROA). The audit committee will be deducted by dividing the total members of the audit committee by the total members of the board of commissioners. The results of this study are profitability and audit committee does not significantly affect audit report lag by having a positive relationship. Audit report lag will increase due to the company's high profitability and the greater proportion of audit committees, resulting in a longer audit process.